2011
DOI: 10.4103/0019-5049.90611
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intraocular pressure following administration of suxamethonium and endotracheal intubation: Influence of dexmedetomidine premedication

Abstract: Background:Use of suxamethonium is associated with an increase in intraocular pressure (IOP) and may be harmful for patients with penetrating eye injuries. The purpose of our study was to observe the efficacy of dexmedetomidine for prevention of rise in IOP associated with the administration of suxamethonium and endotracheal intubation.Methods:Sixty-six American Society of Anaesthesiologists I or II patients undergoing general anaesthesia for non-ophthalmic surgery were included in this randomized, prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…[1011121314] Dexmedetomidine is a highly selective α 2 -adrenoreceptor agonist with α 2 :α 1 binding ratio of 1620:1 compared to 220:1 for clonidine. [2021]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1011121314] Dexmedetomidine is a highly selective α 2 -adrenoreceptor agonist with α 2 :α 1 binding ratio of 1620:1 compared to 220:1 for clonidine. [2021]…”
Section: Discussionmentioning
confidence: 99%
“…[8] Analgesic and sedative properties were found when intrathecal, epidural or intravenous dexmedetomidine was used as an adjuvant in previous studies. [91011121314] There is paucity of studies which have compared the dose equivalence of these two drugs, however various studies have established that the dose of clonidine is 1.5-2 times higher than the dose of dexmedetomidine. [15161718]…”
Section: Introductionmentioning
confidence: 99%
“…But dexmedetomidine 0.4 μg/kg was recommended for this purpose as this dose did not result in significant hypotension. [ 11 ] But another study has shown that even 0.6 μg/kg given IV over 10 min, 10 min before induction, effectively prevented the rise in IOP associated with suxamethonium, laryngoscopy, and intubation with stable hemodynamics. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…There have been few studies on attenuation of the increase in IOP and maintenance of OPP during surgery in a steep Trendelenburg position. Topical application of brimonidine, an α-2 agonist, before general anesthesia resulted in a slight decrease in the intraoperative time-weighted average IOP, by 4 mmHg, and a bolus injection of gabapentin or dexmedetomidine as a premedication before tracheal intubation alleviated the increase in IOP ( 5 6 7 ). The most important factor that causes increased IOP in a steep Trendelenburg position is increased episcleral venous pressure ( 8 ).…”
Section: Introductionmentioning
confidence: 99%